Review: Ann Lewins & Christina Silver (2007). Using Software in Qualitative Research: A Step-by-Step Guide - Berger, Roni (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2008)
Qualitative researchers encounter a diverse plethora of software packages for analyzing text and visual data. This book is designed to help potential users understand the benefits and shortcomings of three main and four additional commonly used such software and based on this understanding, make an informed choice of a software that best fits the needs of particular projects as well as preferences of individual researchers. URN: urn:nbn:de:0114-fqs0901235